2015
DOI: 10.3382/ps/pev244
|View full text |Cite
|
Sign up to set email alerts
|

Starch digestibility, energy utilization, and growth performance of broilers fed corn-soybean basal diets supplemented with enzymes

Abstract: A study was conducted to evaluate the effects of dietary α-amylase and β-xylanase supplementation of corn-soy diets, formulated with or without supplemental phytase, on growth performance, energy utilization, and starch digestibility in broiler chickens. A total of 336 slow-feathering, Cobb × Cobb 500 male broilers were randomly distributed to 6 treatments having 8 replicates of 7 birds each. Birds were fed a common starter diet to d 14 post-hatch (3,050 kcal/kg AMEn, 21.7% CP, 1.05% Ca, and 0.53% nPP). The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 59 publications
5
27
2
4
Order By: Relevance
“…However, some results show that starch cannot be completely digested in the small intestine of broilers due to the lowered net secretion amount of amylase in the duodenum of boilers (Benavent‐Gil & Rosell, 2017; Guo, Zhang, Hu, Li, & Du, 2015; Noy & Sklan, 1995). Similarly, exogenous amylase can refresh the digestive enzyme system in young animals, resulting in an improvement of nutrient digestibility and growth (Gracia, Araníbar, Lázaro, Medel, & Mateos, 2003; Stefanello et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, some results show that starch cannot be completely digested in the small intestine of broilers due to the lowered net secretion amount of amylase in the duodenum of boilers (Benavent‐Gil & Rosell, 2017; Guo, Zhang, Hu, Li, & Du, 2015; Noy & Sklan, 1995). Similarly, exogenous amylase can refresh the digestive enzyme system in young animals, resulting in an improvement of nutrient digestibility and growth (Gracia, Araníbar, Lázaro, Medel, & Mateos, 2003; Stefanello et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Further study is needed to better understand this outcome. However, some hypotheses are related to the type of starch in the diet, based on the stage, the presence of sucrose (simple sugar), or even the possible stimulus caused by resistant starch (Stefanello et al 2015) in SPM that could have contributed to the development of intestinal mucosal, improving how the diets were used and resulting in a compensation and adjustment of WG and FC during this period. The results for carcass yield corroborate those encountered by Beckford & Bartlett (2015), who analyzed substituting up to 30% SPM in the diets of chickens.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the researches supported phytase enzyme and agree with the results of our research Barbosa et al, (2012) found that the addition of phytase, amylase, xylanase, and protease to diets with reducing in energy, calcium, and phosphorus content, give similar result feed intake and weight gain compared with a diet had adequate nutrient levels. Stefanello et al, (2015) showed that the diets supplemented with phytase and with xylanase led to improve growth performance of broiler. Recently, results of Carvalho et al,(2017) and Delezie et al, (2017) showed no synergism effect between phytase and protease supplementation to corn soy broiler diets when examined during age 8 to 21 d of age or when examined at different levels of phytase supplementation (from 350 to 200 FTU/kg), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Selim et al, (2017) under publishing data, recorded that adding xylenase and protease combination to lower 10% of CP and 100 kcal ME/kg broiler diet reduce feeding cost and improve growth performance, carcass traits and meat quality. In this respect, Stefanello et al (2015) showed that corn-soy diets having phytase and supplemented with xylanase led to increased growth performance, AMEn, and starch digestibility in broilers. Also, Herchler et al, (2017) showed the positive effect of the combination between xylanase and phytase on growth performance and breast meat yield in turkey.…”
Section: Introductionmentioning
confidence: 99%